2005
DOI: 10.1086/430619
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Heterogeneity inKlebsiella pneumoniaeStrains Is Associated with Primary Pyogenic Liver Abscess and Metastatic Infection

Abstract: Our results suggest that chromosomal heterogeneity is present in tissue-invasive K. pneumoniae strains. A genotype containing all 3 regions is strongly associated with PLA and metastatic infection. These regions may serve as convenient markers for the rapid diagnosis of emergent tissue-invasive strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
109
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 45 publications
9
109
4
1
Order By: Relevance
“…The assay was evaluated after 24 and 48 hours of incubation, and was performed twice for each isolate. PCR was carried out to assess the presence of yersiniabactin (irp2-1) and Klebsiella ferric iron uptake gene cluster (kfuB) [26,27]. Yeast cell coagglutination in the presence or absence of 1.0% D-mannose was used to detect type 1 fi mbria [28,29].…”
Section: Virulence Associated Traitsmentioning
confidence: 99%
“…The assay was evaluated after 24 and 48 hours of incubation, and was performed twice for each isolate. PCR was carried out to assess the presence of yersiniabactin (irp2-1) and Klebsiella ferric iron uptake gene cluster (kfuB) [26,27]. Yeast cell coagglutination in the presence or absence of 1.0% D-mannose was used to detect type 1 fi mbria [28,29].…”
Section: Virulence Associated Traitsmentioning
confidence: 99%
“…Recent studies have shown that the mucoviscosity-associated gene A (magA) and regulator of mucoid phenotype A (rmpA) are associated with this syndrome [9,[12][13][14]17]. However, we could not ascertain which phenotype and genotype produced invasive K. pneumoniae syndrome in our case.…”
Section: Discussionmentioning
confidence: 66%
“…pneumoniae has been reported to be the most common pathogen causing liver abscess in Korea [6,7]. The incidence of K. pneumoniae infection increases in immunocompromised conditions, such as diabetes mellitus, alcoholism, malignancy, hepatobiliary disease, chronic obstructive pulmonary disease, glucocorticoid therapy and renal failure [6][7][8][9][10][11][12][13][14]. In our case, the In a few cases, K. pneumoniae liver abscess has been associated with metastatic infection at other sites [7,8,[10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we all know, K. pneumoniae is one of the most common and clinically important pathogens worldwide, causing abscess (especially liver abscess) (7,8), and then invades into blood causing multi-sites infection. It can also cause an endogenous infection in diabetes mellitus patients (9-11) as well as cancer patients (12).…”
Section: Discussionmentioning
confidence: 99%